2020
DOI: 10.1002/mds.28113
|View full text |Cite
|
Sign up to set email alerts
|

A 5‐Year Longitudinal Clinical and Magnetic Resonance Imaging Study in Spinocerebellar Ataxia Type 3

Abstract: Background The natural history of neurodegeneration in spinocerebellar ataxia type 3/Machado Joseph disease is still unclear. Here, we built a long‐term longitudinal clinical and neuroimaging study to address this point. Methods Twenty‐three patients with spinocerebellar ataxia type 3/Machado Joseph disease and 22 healthy controls underwent 3T MRI twice 5.0 years apart. T1 and diffusion tensor imaging sequences were obtained. We used T1 multiatlas, diffusion tensor imaging multiatlas, SpineSeg, and CERES‐SUIT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 16 publications
(60 reference statements)
7
18
1
Order By: Relevance
“…The effect size of all other metrics was smaller than that of SARA, although those of cervical spinal cord segment C2 and C3, pons, midbrain, and pallidum were of the same magnitude as that of SARA. The current values are not comparable to effect sizes calculated on the basis of longitudinal data 14,16,36 …”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…The effect size of all other metrics was smaller than that of SARA, although those of cervical spinal cord segment C2 and C3, pons, midbrain, and pallidum were of the same magnitude as that of SARA. The current values are not comparable to effect sizes calculated on the basis of longitudinal data 14,16,36 …”
Section: Discussioncontrasting
confidence: 80%
“…Previous studies in patients with SCA3 showed a pattern of regional brain tissue loss that faithfully reflected the distribution of neurodegenerative changes described in autopsy studies 9‐13 and revealed that regional volume loss already starts in the preataxia stage 9 . Three longitudinal volumetric studies in small numbers of patients with SCA3 suggested that MRI volume is more sensitive to change than clinical scales, which makes MRI volumes promising candidates for biomarkers in clinical trials 14‐16 . This applies in particular to preventive trials in preataxic mutation carriers, as clinical measures lack sensitivity before ataxia onset.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Patients with SCA3 exhibit characteristic ataxia and nystagmus, mild cognitive ( Schöls et al, 2004 ; Braga-Neto et al, 2012 ) and psychiatric symptoms ( Silva et al, 2015 ; Yuan et al, 2019 ). Previous studies in SCA3 mainly focused on the changes in brain structure, such as gray matter atrophy and micro-structural white matter abnormalities ( Meles et al, 2018 ; Guo et al, 2020 ; Piccinin et al, 2020 ). However, an increasing number of studies suggest that, in neural degeneration diseases, there is an alteration in the large-scale brain network rather than only localized dysfunction in a single brain area ( Hillary and Grafman, 2017 ).…”
Section: Introductionmentioning
confidence: 99%